REVITALISASI TEORI NEGARA TERHADAP FENOMENA OLIGARKI POLITIK DAN DINASTI KEKUASAAN DI INDONESIA - muhammad arifudin mz; Salsabila Putri Decha; Wasilatul Jariah; Rudi Santoso (Prodi Ilmu Pemerintahan FISIP UNIBBA, 2026)
Abstract: This study aims to analyze the revitalization of state theory in addressing the phenomena of political oligarchy and power dynasties in Indonesia. Although Indonesia has adopted democratic principles as outlined in the 1945 Constitution, in practice, power is often concentrated in the hands of a few elites, hindering the equitable distribution of power and limiting public participation in political processes. Political dynasties, which involve the repeated inheritance of political power within families or groups, exacerbate inequality, while political oligarchy leads to policies that benefit a small group of elites. This study argues that state theory needs to be revitalized to account for the reality of concentrated power and to ensure that democracy becomes more inclusive, transparent, and responsive to the needs of the people. The research emphasizes the importance of strengthening the democratic process, ensuring accountability, and opening greater spaces for public participation in political decision-making. The revitalization of state theory can contribute to reducing oligarchy and political dynasties in Indonesia's democracy.